2021
DOI: 10.1001/jamasurg.2021.3012
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Image-Based Deep Learning Models to Predict Surgical Complexity and Complications in Abdominal Wall Reconstruction

Abstract: Image-based deep learning models (DLMs) have been used in other disciplines, but this method has yet to be used to predict surgical outcomes.OBJECTIVE To apply image-based deep learning to predict complexity, defined as need for component separation, and pulmonary and wound complications after abdominal wall reconstruction (AWR). DESIGN, SETTING, AND PARTICIPANTSThis quality improvement study was performed at an 874-bed hospital and tertiary hernia referral center from September 2019 to January 2020. A prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…In another study, López-Cano et al argued that the incorporation of artificial intelligence techniques could improve the delivery of patient care by combining and analyzing thousands of abdominal hernia cases and classifying them based on severity and prioritization ( 20 ). Artificial intelligence in abdominal hernia surgery is evident via the research conducted by Elhage et al, which aimed to apply three deep learning models to predict complexity and wound infections after an abdominal hernia procedure ( 21 ). The study outcomes demonstrated that the three image-based models, through computed tomography images, were effective in predicting surgical complexity and more accurate than expert surgeon judgment ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, López-Cano et al argued that the incorporation of artificial intelligence techniques could improve the delivery of patient care by combining and analyzing thousands of abdominal hernia cases and classifying them based on severity and prioritization ( 20 ). Artificial intelligence in abdominal hernia surgery is evident via the research conducted by Elhage et al, which aimed to apply three deep learning models to predict complexity and wound infections after an abdominal hernia procedure ( 21 ). The study outcomes demonstrated that the three image-based models, through computed tomography images, were effective in predicting surgical complexity and more accurate than expert surgeon judgment ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence in abdominal hernia surgery is evident via the research conducted by Elhage et al, which aimed to apply three deep learning models to predict complexity and wound infections after an abdominal hernia procedure ( 21 ). The study outcomes demonstrated that the three image-based models, through computed tomography images, were effective in predicting surgical complexity and more accurate than expert surgeon judgment ( 21 ). These arguments imply that AI has the potential of enhancing multiple processes involved in abdominal hernia surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to provide audio-only evaluations was further bolstered by a large volume of data related to the predictive nature of cross-sectional imaging for abdominal wall reconstruction [ 20 22 ]. In particular, recent work by Elhage et al have demonstrated that findings on cross-sectional imaging are predictive of need for advanced reconstruction techniques (e.g., myofascial advancement flaps), as well as postoperative outcomes related to surgical site infections [ 23 ]. As such, we have broadened our options for preoperative telemedicine evaluations to include audio-only options for patients presenting for ventral or inguinal hernia repair consultations that imaging-based confirmation available for review at the time of consultation.…”
Section: Discussionmentioning
confidence: 99%
“…2021;156:933-940. 5 The authors applied image-based deep learning to predict complexity, defined as the need for component separation, and pulmonary and wound complications after abdominal wall reconstruction. They concluded that image-based deep-learning models using routine, preoperative computed tomography images were successful in predicting surgical complexity and more accurate than expert surgeon judgment.…”
Section: Development and Validation Of Image-based Deep Learning Mode...mentioning
confidence: 99%